Lenvatinib plus pembrolizumab versus sunitinib as first-line treatment of patients with advanced renal cell carcinoma (CLEAR): extended follow-up from the phase 3, randomised, open-label study. Issue 3 (March 2023) - Choueiri, Toni K; Eto, Masatoshi; Motzer, Robert; De Giorgi, Ugo; Buchler, Tomas; Basappa, Naveen S; Méndez-Vidal, María José; Tjulandin, Sergei; Hoon Park, Se; Melichar, Bohuslav; Hutson, Thomas; Alemany, Carlos; et al.
Summary: Background: In the primary analysis of the CLEAR study, lenvatinib plus pembrolizumab significantly improved progression-free survival and overall survival versus sunitinib in patients with advanced renal cell carcinoma (data cutoff Aug 28, 2020). We aimed to assess overall survival based on 7 months of additional follow-up. Methods: This is a protocol-prespecified updated overall survival analysis (data cutoff March 31, 2021) of the open-label, phase 3, randomised CLEAR trial. Patients with clear-cell advanced renal cell carcinoma who had not received any systemic anticancer therapy for renal cell carcinoma, including anti-vascular endothelial growth factor therapy, or any systemic investigational anticancer drug, were eligible for inclusion from 200 sites (hospitals and cancer centres) across 20 countries. Patients were randomly assigned (1:1:1) to receive lenvatinib (20 mg per day orally in 21-day cycles) plus pembrolizumab (200 mg intravenously every 21 days; lenvatinib plus pembrolizumab group), lenvatinib (18 mg per day orally) plus everolimus (5 mg per day orally; lenvatinib plus everolimus group [not reported in this updated analysis]) in 21-day cycles, or sunitinib (50 mg per day orally, 4 weeks on and 2 weeks off; sunitinib group). Eligible patients were at least 18 years old with a Karnofsky performance status of 70 or higher. A computer-generated randomisation scheme was used, and stratification factors were geographical region and Memorial Sloan Kettering Cancer Center prognostic groups. The primary endpoint was progression-free survival assessed by independent imaging review according to Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST v1.1). In this Article, extended follow-up analyses for progression-free survival and protocol-specified updated overall survival data are reported for the intention-to-treat population. No safety analyses were done at this follow-up. This study is closed to new participants and is registered with ClinicalTrials.gov, NCT02811861 . Findings: Between Oct 13, 2016, and July 24, 2019, 1417 patients were screened for inclusion in the CLEAR trial, of whom 1069 (75%; 273 [26%] female, 796 [74%] male; median age 62 years [IQR 55–69]) were randomly assigned: 355 (33%) patients (255 [72%] male and 100 [28%] female) to the lenvatinib plus pembrolizumab group, 357 (33%) patients (275 [77%] male and 82 [23%] female) to the sunitinib group, and 357 (33%) patients to the lenvatinib plus everolimus group (not reported in this updated analysis). Median follow-up for progression-free survival was 27·8 months (IQR 20·3–33·8) in the lenvatinib plus pembrolizumab group and 19·4 months (5·5–32·5) in the sunitinib group. Median progression-free survival was 23·3 months (95% CI 20·8–27·7) in the lenvatinib plus pembrolizumab group and 9·2 months (6·0–11·0) in the sunitinib group (stratified hazard ratio [HR] 0·42 [95% CI 0·34–0·52]). Median overall survival follow-up was 33·7 months (IQR 27·4–36·9) in the lenvatinib plus pembrolizumab group and 33·4 months (26·7–36·8) in the sunitinib group. Overall survival was improved with lenvatinib plus pembrolizumab (median not reached [95% CI 41·5–not estimable]) versus sunitinib (median not reached [38·4–not estimable]; HR 0·72 [95% CI 0·55–0·93]). Interpretation: Efficacy benefits of lenvatinib plus pembrolizumab over sunitinib were durable and clinically meaningful with extended follow-up. These results support the use of lenvatinib plus pembrolizumab as a first-line therapy for patients with advanced renal cell carcinoma. Funding: Eisai and Merck Sharp & Dohme.